Continuous flow gas phase photoreforming of methanol at elevated reaction temperatures sensitised by Pt/TiO2. Issue 6 (11th October 2016) - Caravaca, A.; Daly, H.; Smith, M.; Mills, A.; Chansai, S.; Hardacre, C.
Abstract : Gas phase photoreforming of methanol using a Pt/TiO2 photocatalyst has been performed under flow conditions at elevated temperatures. Abstract : Gas phase photoreforming of methanol using a Pt/TiO2 photocatalyst has been performed under flow conditions at elevated temperatures. Comparing the activity of the reforming process as a function of temperature under dark and irradiated conditions shows a significant enhancement in the rate of H2 production using the photo-assisted conditions at temperatures between 100–140 °C. At higher temperatures, the effect of irradiation is small with the process dominated by the thermal process. Deactivation of the catalyst was observed under irradiation but the catalyst was easily regenerated using an oxygen treatment at 120 °C. Diffuse reflectance infra-red Fourier transform spectroscopy (DRIFTS) showed that the activity of the catalyst could be correlated with the presence of the photogenerated trapped electrons. In addition, lower amounts of CO adsorbed on Pt, compared to those observed in the dark reaction, were found for the UV-irradiated systems. It is proposed that CO and adsorbed intermediates, such as formate, can act as inhibitors in the photoreforming process and this is further supported by the observation that, before and after the regeneration process in O2, the CO and surface adsorbed organic intermediate products are removed and the activity is recovered.